EKSPERIMENTASI MODEL PEMBELAJARAN TEAMS ASSITED INDIVIDUALIZATION (TAI) DAN NUMBERED HEADS TOGETHER (NHT) DENGAN PENDEKATAN KONTEKSTUAL PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DITINJAUDARI KREATIVITAS BELAJAR SISWA - Awalia, Kurnia; Budiyono, Budiyono; Sujadi, Imam (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from students learning creativity. The learning models compared were TAI with contextual approach, NHT with contextual approach, and direct instruction Â with contextual approach. The type of the research was a quasi-experimental research. The populations were all students of Junior High School in Gemolong subdistrict. Sampling was done by stratified cluster random sampling. The samples were students of SMPN 1 Gemolong, SMPN 2 Gemolong, and SMP Muh 9 Gemolong. The instruments used were mathematics achievement tests and creativity questionnaire. The data was analyzed using unbalanced two-ways anova. The conclusions were as follows. (1) TAI with contextual approach gives better mathematics achievement than NHT with contextual approach, TAI with contextual approach gives better mathematics achievement than direct instruction with contextual approach, NHT and direct instruction with contextual approach have the same mathematics achievement. (2) For students with high and medium learning creativity have the same mathematics achievement. Mathematics achievement of students who have high and medium learning creativity was better than students who have low learning creativity. (3) For students who have high learning creativity, all learning models gives the same mathematics achievement. (4) For students who have medium learning creativity, all learning models gives the same mathematics achievement. (5) For students who have low learning creativity, TAI and NHT with contextual approach gives the same mathematics achievement. NHT and direct instruction with contextual approach gives the same mathematics achievement. TAI with contextual approach gives better mathematics achievement than direct instruction with contextual approach.Keywords: TAI, NHT, contextual approach, learning achievement, learning creativity.